Occupational exposure to contaminated biological material: perceptions and feelings experienced among dental students - Camila PINELLI; Luis Felipe Garcia Leal MOUTA
INTRODUCTION: Dental students may be a particularly vulnerable group exposed to the risk of acquiring infections through occupational injuries.OBJECTIVE: To investigate the perceptions with regard to their occupational exposure to potentially infectious biologic materials.MATERIAL AND METHOD: Interviews were conducted by means of a script with open questions. The speeches were recorded, transcribed and qualitative analysis was performed with the aid of QUALIQUANTISOFT® software. The Collective Subject Discourse (CSD) was obtained.RESULT: The feeling most frequently experienced was related to the fear of contagion. Most accidents occurred during the handling of sharp dental instruments. Respondents attributed the occurrence of accidents especially the lack of attention, carelessness while handling sharp instruments, and lack of use of Personal Protective Equipment. As regards the measures taken right after the exposure, they "washed the local area". Other respondents reported they "continued the dental treatment". They complained mostly about the fear of having been infected, and because they had to leave the faculty to take blood exams for HIV screening. As part of the learning experience the injured reported they paid more attention when handling sharp instruments. The students informed that any type of injury due to contact with contaminated material must be notified. However, they were neglectful about reporting their own injury.CONCLUSION: Education strategies for preventive measures related to occupational exposure must be restructured, because the knowledge and the fear of contagion among dental students were not always sufficient for a complete adherence to treatment protocols and notification.